ANALYSIS OF FACTORS AFFECTING RAW GOODS IN INDONESIA SINCE 1986-2021 - Kokop, Rohmadoni; Lubis, Firstly Ramadhona Amalia (Jurnal Mebis, 2023)
In Indonesia, the demand for raw goods continues to increase along with national and international needs, making production continue to increase and this makes economic growth continue to increase, but inversely proportional to the availability of raw goods in nature which is increasingly dwindling and it is feared that it does not have raw goods spare parts, so the government carries out policies related to this phenomenon by allowing more processing of raw goods into semi-finished goods so that More maximally in handling these problems and increasing the value of investment and export activities. In addition, investment adds to existing resources so as to create relations between countries with cooperation and use the prevailing exchange rate. In this study, it is known that the influence of raw goods on economic growth is positive with other factors such as investment activities, exports, exchange rates that make economic growth more positive than the previous year. In this method, using the var model in research where previous research was carried out previously through secondary data collection methods and separated in detail according to year. Management uses apalkasi in conducting research with var more helps get information shouting data that is processed.from the results of the sarsenerity test it is found that all variables except for one varibael, namely the Export variable (EKS) because at the level or first difference do not have a stationary value.the optimal leg test leg is in the maximum second leg.in the stability test all have a stable intention.impulse response has a positive and negative effect on variables except against investment while in the Variance Decomposition test increased every period. The production of raw goods has a negative effect at the beginning of the production period but often over time it has a positive effect on economic growth.